MASUKKIRI TRADITION AS A MEANS OF INTERNALIZING ISLAMIC EDUCATIONAL VALUES IN THE BUGIS COMMUNITY OF PAGATAN, TANAH BUMBU: English - Fikri Haekal Akbar; Miftahul Aula Sa'adah (CARITA: Jurnal Sejarah dan Budaya, 2025)
The Masukkiri tradition of the Bugis community in Pagatan, Tanah Bumbu, represents a unique convergence of local culture and Islamic educational values. Rooted in oral literary practices and poetic recitations of Mawlid al-Barzanji, Masukkiri is more than just a performance art—it is a pedagogical vehicle for transmitting faith, moral values, social cohesion, and cultural appreciation. This study explores how Masukkiri functions as an internalizing force of Islamic teachings, particularly through the collective chanting of praises for the Prophet Muhammad, remembrance of Allah’s names, and the symbolic acts embedded in its ceremonial practices. Using a descriptive qualitative method within a phenomenological framework, fieldwork was conducted in selected villages where the tradition is still preserved. The research reveals that Masukkiri cultivates Islamic educational values among its participants, especially the elderly, while facing generational challenges in sustainability. Through detailed analysis, this paper illustrates how Masukkiri contributes to communal identity and religious consciousness, advocating for its revitalization as both a spiritual and cultural heritage in contemporary Islamic education.